2015
DOI: 10.1111/eea.12317
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, behavior impairment, and repellence of essential oils from pepper‐rosmarin and patchouli to termites

Abstract: Plant essential oils are potential sources of insecticidal compounds, but have rarely been explored for their effect on termites. In the present study, we assessed the chemical composition of essential oils of Lippia sidoides Cham. (pepper‐rosmarin; Verbenaceae) and Pogostemon cablin (Blanco) Benth. (patchouli; Lamiacaeae) and evaluated their toxicity, behavioral impairment, and repellence to termite species of the genera Amitermes and Microcerotermes (Isoptera: Termitidae: Termitinae). The main components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
1
11
0
3
Order By: Relevance
“…These results show the potential of the use of this compound for the control of the A. aegypti mosquito. Our results corroborate those of previous studies that have shown that EOs from plants have an efficient insecticidal action on several pests . However, few studies have evaluated the potential insecticidal and sublethal effects of these compounds on populations of resistant insects, including A. aegypti .…”
Section: Discussionsupporting
confidence: 91%
“…These results show the potential of the use of this compound for the control of the A. aegypti mosquito. Our results corroborate those of previous studies that have shown that EOs from plants have an efficient insecticidal action on several pests . However, few studies have evaluated the potential insecticidal and sublethal effects of these compounds on populations of resistant insects, including A. aegypti .…”
Section: Discussionsupporting
confidence: 91%
“…[18] Smelling a unique woody odor, the essential oil of P. cablin, usually known as patchouli oil, is of great industrial importance [19] and has been reported showing bioactivities against insect pests. There are some reports recording the insecticidal activities of P. cablin against mosquito vectors, [20] cockroach, [21] termites, [22,23] armyworm, [24] and ants, [25,26] as well as repellent effects on termites, [22,23] sweetpotato whitefly, [27] urban ants [25] and the cockroach. [21] And a recent paper [26] reported that P. cablin essential oil showed behavioral impairment on leaf-cutting ants.…”
Section: Introductionmentioning
confidence: 99%
“…Individual behaviours of treated and untreated ants were evaluated according to the procedure of Bacci et al (2015).…”
Section: Behaviourmentioning
confidence: 99%